Applying the Food Choice Process Model to Ultra-Processed Food Consumption: The Role of Dietary Globalization and Quality Perceptions - Eda Luga; Gentjan Mehmeti (European Scientific Journal, ESJ, 2026)
This study examines the determinants of ultra-processed food (UPF) consumption frequency among young adults within the Food Choice Process Model (FCPM), integrating macro-level (dietary globalization) and micro-level (perceptions of food quality, environmental awareness, and media exposure) influences. Data were collected in 2025 from a sample of 310 young adults to understand consumer dietary behavior. Ordinal logistic regression analysis was employed to test the hypothesized predictors of UPF consumption frequency.The results indicate that dietary globalization is positively and significantly associated with UPF consumption, suggesting that greater exposure to international dietary patterns increases the likelihood of consuming UPFs. In contrast, negative perceptions of international food quality are significantly and negatively associated with consumption frequency, indicating that unfavorable quality evaluations can act as a deterrent. Environmental awareness and exposure to internet and social media content do not emerge as statistically significant predictors, implying that, in this context, broader structural influences and individual evaluative judgments may play a more prominent role than sustainability concerns or digital media exposure.Overall, UPF consumption among young adults appears to be primarily shaped by globalization-related dietary exposure and perceptions of food quality, rather than by environmental or media-related factors. These findings provide empirical insight into the structural and cognitive drivers of contemporary dietary behavior and offer implications for public health strategies aimed at reducing UPF consumption.